Automation use and dis-use in golf: The impact of distance measuring devices on trust in technology and confidence in determining distance - Dithurbide, L.; Neyedli, H.; Swinimer, J.; Macfarlane, J. (Frontiers in Psychology, 2021)
An athlete`s decision to use technology depends on trust in the automation, and confidence in their abilities. Distance measuring devices (DMD) are used in golf to estimate yardage. The purpose of these studies was to examine how DMD usage affects trust in the DMD, confidence in determining yardage manually, and golf performance over time. In study 1, DMD non-users played four rounds of golf, two with the DMD and two without. In study 2, DMD users played five rounds, three with the device, and two without. Participants` trust in automation, confidence, and performance were recorded by online survey at baseline and following each round. Giving a DMD to non-users influenced trust in automation and confidence. When DMD users relinquished the device, confidence decreased briefly but rebounded quickly, trust in automation was unaffected. Performance was unchanged in both groups. These studies provide information about how confidence in abilities and trust in automation interact.